Implementation of an interactive virtual microscope laboratory system in teaching oral histopathology - Jia Qing; Gu Cheng; Xiao-Qi Ni; Yi Yang; Wei Zhang; Zhi Li (Scientific Reports, 2022)
Abstract Laboratory course acts as a key component of histopathology education. Recent trends of incorporating visual and interactive technology in active and inquiry-based learning pedagogical methods have led to significant improvement of histopathology laboratory courses. The present work aimed to describe interactive virtual microscope laboratory system (IVMLS) as a virtual platform for teaching histopathology in order to improve the quality and efficiency of teaching. The system is based on interactive technology and consists of interactive software, slide-reading software, teaching resources and integrated auxiliary equipment. It allows real-time interaction between teachers and students and provides students with a wealth of learning and review materials. In order to evaluate the effectiveness of the system, we conducted a comparative study with the use of light microscope (LM) as a method. Specifically, we compared the results of six assignments and one laboratory final exam between IVMLS group and LM group to analyse the impact of IVMLS on students' academic performance. A questionnaire survey was also conducted to obtain students' attitudes and views on this system. There was no overall difference in assignment performance between IVMLS group and LM group. But laboratory final test grades increased from a mean of 62% (43.8–80.0, 95% CI) before to 83% (71.0–94.2, 95% CI) after implement IVMLS, suggesting highly significant (p < 0.001) improvement on students' histopathology laboratory performance. Feedback of the questionnaire was positive, indicating that students were satisfied with the system, which they believed improved student communication and teacher-student interaction, increased learning resources, increased their focus on learning, and facilitated their independent thinking process. This study proves that IVMLS is an efficient and feasible teaching technology and improves students' academic performance.